Motivasi, Stigma dan Coping Stigma pada Perempuan Bercadar - Rahman, Alif Fathur; Syafiq, Muhammad (Universitas Negeri Surabaya, 2017)
Full-face veil is a head scarf with a face cover which only leave eyes exposed used by Muslim women as accompanied with wearing long hijab and black dominated clothes covering body. A full-face veil has some kinds such as niqab and burqa. Women with full-face veil generally become the target of stigma. This study explores full-face veiled women’s experiences including their motivation that encourage them to wear it, the stigma they face, and how they cope with the stigma. Five women who wear full-face veils involved in this study. Data collected using semi-structured interviews and analyzed using interpretative phenomenological analysis. The result shows that wearing full-face veil is motivated primarily by religious loyalty and for guarding them from sexual objectification. Their strong religious loyalty make them ready to face stigma labelled by their surrounding society such as accused as a fanatic,a member of terrorist group, and being avoided by their surrounding people. The strategies they use to cope with the stigma cover internal and external strategies. The internal strategies consist of ignoring the stigma and taking the view that the stigma is caused by the surrounding society’s misunderstanding. Meanwhile, the external strategies include of taking effort to clarify and give the explanation to revise the misunderstanding,as well as participating in neighborhood activities.Key words: Muslim women, full-face veil, stigma, coping stigmaAbstrak: Cadar adalah penutup wajah perempuan muslim yang menutup wajah kecuali kedua mata digunakan dengan jilbab dan baju kurung panjang serta didominasi warna gelap yang menutup seluruh tubuh. Perempuan bercadar biasanya rentan dengan stigma. Penelitian ini membahas pengalaman perempuan bercadar meliputi motivasi bercadar, bentuk stigma yang mereka hadapi, dan bagaimana cara mereka menghadapi stigma. Data dikumpulkan menggunakan wawancara semi-terstruktur dan dianalisis menggunakan analisis fenomenologi interpretif. Penelitian ini mengungkap tiga tema yaitu motivasi bercadar, bentuk stigma yang dialami, dan strategi untuk menghadapi stigma. Hasil penelitian ini menunjukkan bahwa motivasi bercadar muncul dari ketaatan dalam beragama dan keinginan untuk menghindarkan diri dari objektivikasi seksual. Hal ini membuat mereka siap menghadapi stigma seperti dianggap fanatik, anggota kelompok teroris, dan dihindari oleh orang-orang di sekitarnya. Strategi menghadapi stigma yang ditempuh partisipan dapat digolongkan menjadi dua, yaitu strategi internal dengan cara mengabaikan dan memaklumi pandangan negatif masyarakat sekitar, dan strategi eksternal melalui pemberian penjelasan sebagai klarifikasi dan ikut melibatkan diri dalam kegiatan bersama masyarakat sekitar.